1993
DOI: 10.1039/c39930001807
|View full text |Cite
|
Sign up to set email alerts
|

Activation of metal-bound salicylaldoximes

Abstract: Neutral, bis-complexes of oxovanadium(iv) with salicylaldoximes and salicylketoximes react with a range of nitriles t o afford a novel organic ligand type; the prototypical reaction product [VV02{ C6H4(0)CH=N-OC(Me)=NH}] is characterised by single crystal X-ray diffraction and spectroscopic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…26 and also later byZerbib et al 27 who observed complicated processes between oxovanadium() aldoxime and ketoxime complexes, for example [VO{HON᎐ ᎐ CH(O)C 6 H 4 } 2 ], under treatment with acetonitrile. In the course of oxidation of the vanadium(), loss of one oxime ligand and addition of MeCN, the iminoacyl oxovanadium complex [VO 2 {NH᎐ ᎐ C(Me)ON᎐ ᎐ CH(O)C 6 H 4 }] is formed.…”
mentioning
confidence: 86%
“…26 and also later byZerbib et al 27 who observed complicated processes between oxovanadium() aldoxime and ketoxime complexes, for example [VO{HON᎐ ᎐ CH(O)C 6 H 4 } 2 ], under treatment with acetonitrile. In the course of oxidation of the vanadium(), loss of one oxime ligand and addition of MeCN, the iminoacyl oxovanadium complex [VO 2 {NH᎐ ᎐ C(Me)ON᎐ ᎐ CH(O)C 6 H 4 }] is formed.…”
mentioning
confidence: 86%
“…[13,14] Amongst these the most notable one was described by Kukushkin et al: [15] from the reaction of the platinum(II) complex [PtCl 2 ((CH 3 ) 2 Cϭ NOH) 2 ] with m-chloroperoxybenzoic acid in acetone the N,O-chelating complex [PtCl 2 {OC(CH 3 ) 2 ONϭC(CH 3 ) 2 } 2 ] was obtained which contains two five-membered PtϪNϪOϪCϪO rings. The most likely explanation for the formation of the product was proposed to be the coordination of acetone molecules at vacant sites on platinum, followed by ring closure with neighbouring N-coordinated monodentate oxime ligands.…”
Section: Resultsmentioning
confidence: 99%
“…1(e)] with the formation of a novel organic ligand. 23 The assignment of (formal) metal oxidation state in the dimeric compounds can be non-trivial as the magnetic distinction between vanadium-() and -() is no longer present if there is strong antiferromagnetic coupling between the oxovanadium() centres. The identification of the dimeric species [Fig.…”
mentioning
confidence: 99%